2022
DOI: 10.1111/lam.13633
|View full text |Cite
|
Sign up to set email alerts
|

Selection of ACC deaminase positive, thermohalotolerant and drought tolerance enhancing plant growth-promoting bacteria from rhizospheres of Cyamopsis tetragonoloba grown in arid regions

Abstract: Significance and Impact of the Study: Plant growth-promoting bacteria (PGPBs) are widely acknowledged for rescuing crop productivity in regions experiencing biotic/abiotic stresses. However, their implementation in arid regions experiencing severe drought stress has remained elusive. It is reasoned that PGPBs must have extremophilic traits and plant growth promotion capabilities for their application in arid regions. Here we report on targeted selection of bacterial isolates that express ACC deaminase and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…ACC-deaminase-producing PGPR has been considered in recent years an effective plant probiotic in plant roots. Several studies [ 22 , 23 , 24 , 38 , 39 , 40 , 55 , 56 , 57 , 58 , 59 ] have shown that bacteria that produce ACC deaminase and are introduced to the rhizosphere of plants can decrease the amount of ethylene produced by plants under stress. This reduction helps plants resist stress while also promoting growth by using the produced α-ketobutyrate and ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…ACC-deaminase-producing PGPR has been considered in recent years an effective plant probiotic in plant roots. Several studies [ 22 , 23 , 24 , 38 , 39 , 40 , 55 , 56 , 57 , 58 , 59 ] have shown that bacteria that produce ACC deaminase and are introduced to the rhizosphere of plants can decrease the amount of ethylene produced by plants under stress. This reduction helps plants resist stress while also promoting growth by using the produced α-ketobutyrate and ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…Although quantitative synthesis was impossible due to limited available studies, we excluded numerous acdS gene studies for lacking log 2 fold change reporting. Many of these studies validated the presence of the ACC deaminase gene (acdS) through PCR in bacterial strains from the rhizosphere of plants like Cyamopsis tetragonoloba and Pennisetum glaucum L., showcasing their potential as PGPR in enhancing plant growth under water stress conditions (Goyal et al, 2022;Murali et al, 2021). It is widely recognized that microorganisms can reduce ethylene levels in the plant through the ACC deaminase enzyme.…”
Section: B a Figurementioning
confidence: 99%
“…Phytohormones such as indole acetic acid (IAA), gibberellins, ABA, ethylene, and cytokinin are organic chemical messengers that coordinate cellular events in plants and, therefore, play a crucial role in plant development and drought stress tolerance [44]. These phytohormones are generally produced by plants; however, they also produced by some plant-associated microorganisms.…”
Section: Microbial Production Of Phytohormonementioning
confidence: 99%